Development, validation, and application of a simple UPLC–MS/MS method for simultaneous quantification of five traditional antipsychotics in human plasma. (6th May 2021) - Fan, Liju; An, Jing; Cui, Yanjun; Dong, Zhanjun
Abstract: A UPLC–MS/MS method was developed to determine the levels of five traditional antipsychotics (APs) (chlorprothixene, perphenazine, fluphenazine, thioridazine, and promethazine) in human plasma with carbamazepine as the internal standard. Samples were extracted using simple liquid–liquid extraction (ethyl acetate/methyl tert ‐butyl ether, 2:3 v/v); then the analytes were subjected to gradient elution chromatography with a mobile phase composed of 0.1% formic acid in water and acetonitrile. The analytes were separated using a Waters XBridge BEH C18 column (100 × 2.1 mm, 2.5 μm). The linear ranges of chlorprothixene, perphenazine, fluphenazine, thioridazine, and promethazine are 2–250 ng/mL, r  > 0.995. The limit of quantitation is 2 ng/mL, and the limit of detection is in the range of 0.1–0.5 ng/mL. The inter‐day and intra‐day relative standard deviations are less than 10%, and the relative errors are in the range of −5.70 to 7.20%. The recoveries of the five drugs are in the range of 70–109%. The results of methodology verification indicate that this method is simple, economical, sensitive, and suitable for the simultaneous quantification of five traditional APs in human plasma.